Tegucigalpa, espejismo de la modernidad : el impacto de los discursos liberal y neoliberal sobre la capital de Honduras (siglos XIX y XX) - Daniela Navarrete Cálix (Les Cahiers ALHIM)
This work is a diachronic comparison at the city of Tegucigalpa, capital of Honduras, and the urban transformations carried out in two political and historical moments: the called Liberal Reform on the XIXth century and the neo-liberal politics conducted at the end of the XXth century. The question is to correlate the two modernizations speeches and their urban impact in Tegucigalpa, made by the Honduran State on the XIXth century, and by the private sector on the XXth. At the end of the XIXth, the liberal speech looked for the creation of the Honduran Nation through out modern measures in terms of politics, economy and society. This political will was reflected in the urban landscape of Tegucigalpa, the new capital, political and administrative headquarter of the country. Instead of this, the neo-liberal speeches of the XXth century argued the need of renew the political and economical structure of the State. They looked for withdrawing the government initiative as development enhancer letting other initiatives occupied this roll. In both moments, these politics had a considerable impact in the urban transformations produced in Tegucigalpa. The modernity wished by the Honduran authorities and translated in urban politics, is desired or suffered by its inhabitants?